“Does Timing of Surgery Affect Outcome In Laparoscopic Cholecystectomy for Acute Cholecystitis?” - SAMA MUKHTAR, NADEEM AHMAD, MUMTAZ AHMAD KHAN, RAKHSHANDA RASHID (Journal of Fatima Jinnah Medical University, 2018)
Background: Gallstone disease is a common problem and many patients present with acute cholecystitis (AC). The policy of laparoscopic cholecystectomy (LC) in AC needs to be evaluated in our set up. Objectives: To study the effect of timing of surgery on the outcome in laparoscopic cholecystectomy for acute cholecystitis. Materials and Methods: All patients presenting with gallstone disease to our institution, from June 1, 2009 to May 31, 2010 underwent laparoscopic cholecystectomy on first available elective list, irrespective of duration of symptoms and data was analyzed. Results: A total of 156 patients presented with gallstone disease. Mean age was 49.50 and male to female ratio of 1:5.5. AC was diagnosed in 49 (31.41%). Majority of patients (n-25, 51.02%) with AC presented in 4-7 days duration. Mean operating time was 54.08 minutes in chronic cholecystitis (CC), 55.83 minutes in LC performed with 72 hours of onset and 73.2 minutes in patients operated later for AC. Conversion rate to open cholecystectomy was 9.09% in LC for AC within 72 hours of onset, 66.66% if operated during 4-7 days duration. In Chronic cholecystitis conversion rate was 4.67% while the same was 4.28% in patients after six weeks after resolution of AC. Morbidity, complications, conversion rate and postoperative stay was significantly higher in male patients presenting during 4-7 days after the onset of AC. Conclusion: LC is feasible and safe in AC, if performed early. It has similar morbidity and mortality pattern compared to patients undergoing LC for CC or patients who are operated six weeks after an acute attack of AC. However LC after 72 of onset of symptoms is associated with increased operating time, morbidity and complication rate.